Technical Standard Analysis of Health SPM Achievements in Productive Age Health Services in Bondowoso District Community Health Center Based on The Donabedian Model - Lia Dewiyanti; Nuryadi Nuryadi (Lambung Mangkurat University, 2025)
Background: The Bondowoso Regency Government through the Health Office has implemented SPM Health in ensuring the quality of basic health services in the Bondowoso Regency area. The low achievement of health services for productive age groups needs to be studied from the beginning of the implementation of health services to the overall performance results with a system approach to determine what factors influence the achievement of SPM health services at productive age groups. Based on the Donabedian model, the quality of health services is influenced by indicators of structure/input, process and outcome/results. Purposes: analyzing technical standards (HRD standards and standards for quantity and quality of goods) against the achievement of minimum health service standards in health services for productive ages at the Bondowoso District Health Center based on the Donabedian Model. Method: This study is a quantitative study with a cross-sectional approach. The sample in this study was 25 work teams in 25 health centers in Bondowoso Regency. Data analysis in this study used ordinal logistic regression. Results: This study shows that the influence of technical standards (HR standards and standards for the quantity and quality of goods) on the achievement of minimum health service standards in health services for productive ages at the Bondowoso Health Center p value <0.05.